2021
DOI: 10.1177/00469580211048701
|View full text |Cite
|
Sign up to set email alerts
|

A WhatsApp-Based Intervention to Improve Maternal Social Support and Maternal–Child Health in Southern Brazil: The Text-Message Intervention to Enhance Social Support (TIES) Feasibility Study

Abstract: Participatory learning and action cycles with women’s groups have been recommended by the WHO to promote maternal and newborn health, but few studies have tested its feasibility and acceptability in mobile health (mHealth) interventions among mothers of toddlers. This was a mixed-method feasibility assessment of an 8-week WhatsApp-based maternal support group for mothers of toddlers (12–18 months of age) enrolled in a birth cohort study in Southern Brazil. Daily messages and weekly activities were sent by mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Online supplemental file 6 shows the results of the risk of bias assessment for the non-RCTs. Among the 11 quasi-experimental studies, 4 had a serious risk of bias,53–56 4 had a moderate risk57–60 and 3 were assessed as low risk 61–63. The two observational studies did not have clear information on confounding variables and blinding of the outcome assessors 64 65.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Online supplemental file 6 shows the results of the risk of bias assessment for the non-RCTs. Among the 11 quasi-experimental studies, 4 had a serious risk of bias,53–56 4 had a moderate risk57–60 and 3 were assessed as low risk 61–63. The two observational studies did not have clear information on confounding variables and blinding of the outcome assessors 64 65.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies assessed the roles of mHealth in self-reported levels of depressive symptoms 37 44 45 49 50 54–56 60 61 63 70. Five studies found a positive effect, four studies had mixed findings and three studies found no significant effect (GRADE certainty of evidence: low).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group discussions through the WhatsApp group, where participants in the group can listen wherever they are, and they are freer to ask questions in the chat group forum and are not limited by time (Patel et al, 2018;Pham et al, 2014;Puertas-Gonzalez et al, 2021). Whatsapp group-based services are really good to be used to provide social support during pregnancy, in the WhatsApp group pregnant women are calmer after getting assistance and discussing through the WhatsApp group (Trude et al, 2021). Health education can be used as an appropriate method to improve the welfare of the community (Ningsih et al, 2021).…”
Section: The Effect Of Whatsapp Media To Reduce the Anxietymentioning
confidence: 99%
“…WhatsApp use is frequent among Brazilians 7 , and it is being increasingly used as a health communication tool in digital mental health programs 4,7 . The widespread of mobile phones in low-and middle-income countries (LMICs) has created an incentive for the use of WhatsApp in primary health care 8 .…”
Section: Introductionmentioning
confidence: 99%